The regulatory lag in English Intensive Course: How do the lecturers manage AI in the classroom? - Rohim, Agil Abdur (Proceeding of International Conference on Islamic Education (ICIED), 2025)
The rapid proliferation of Artificial Intelligence (AI) technology has fundamentally disrupted higher education, creating a pronounced incongruity between technological pace and institutional regulatory response. This study investigates the resulting policy vacuum within English Intensive Courses (EICs) in Indonesia, analyzing the regulatory landscape (RQ1), current instructional practices (RQ2), and the emergent pedagogical strategies (RQ3) employed by ELT lecturers to manage AI integration. Employing a qualitative descriptive approach utilizing sequential semi-structured interviews with seven English intensive lecturers in Indonesia, the findings confirm the absence of fixed, centralized policies, leading to highly fragmented, course-level implementation. Lecturers primarily managed AI through a proactive recalibration of assessment toward higher-order thinking, mandatory process documentation (scaffolding), and the integration of critical AI literacy into the curriculum. This reliance on individual instructor agency, however, generates significant burdens regarding monitoring and ethical arbitration, indirectly exacerbating risks related to academic integrity, institutional consistency, and equity for non-native English speakers. The study concludes that lecturer professional expertise is currently compensating for systemic failures in institutional policy, necessitating urgent standardization and systemized professional development.